Fermented Erigeron breviscapus flavonoids: anti-pseudorabies virus efficacy and mechanisms in vitro and in vivo - Zhang, Ying; Li, Ting; Yang, Chunkun; Pan, Qiong; Pan, Changxu; Zhang, Xue; Zhang, Ying; Shu, Xianghua; Wang, Zheng; He, Zhenghong; Qu, Zichen; Song, Chunlian (Frontiers in Veterinary Science, 2025)
IntroductionErigeron breviscapus exhibits anti-inflammatory properties, protects neuronal cells and enhances immune function. Modern traditional Chinese medicine fermentation techniques can increase the bioactive compound content in Erigeron breviscapus. However, its potential therapeutic effects against the porcine pseudorabies virus (PRV) remain unclear.MethodsA PRV infection model was established in mouse trigeminal ganglion (TG) cells to determine the optimal antiviral mode of action of flavonoids from fermented Erigeron breviscapus (FEBF). Additionally, a PRV-infected rat model was developed to evaluate the in vivo antiviral efficacy of FEBF.ResultsFEBF demonstrated a higher protective rate and a lower viral copy number compared to unfermented E. breviscapus flavonoids (EBF). The protective effect was most pronounced under toxicological and inhibitory conditions, surpassing the blocking effect. PRV infection upregulated TLR4, MyD88, and NF-κB p65 protein expression during the pre-infection phase, followed by their downregulation after 12 h. FEBF regulated PRV-induced changes in protein expression, restoring them to near-normal levels by 36 h. In vivo assessments of pathological injury, PRV viral load, neuronal count, and neuronal apoptosis indicated that FEBF provided superior neuroprotection compared to both Minocycline (MINO), a broad-spectrum neuroprotective drug, and unfermented EBF. Mechanistic studies further revealed that FEBF modulated microglial polarization and regulated the inflammatory cytokines IL-6, TNF-α, IL-4, and IL-10.ConclusionThese findings demonstrate that FEBF exhibits significant antiviral effects against PRV in both in vitro and in vivo models. FEBF represents a promising candidate for the development of anti-PRV therapeutics.